ETIKA PELAYANAN KRISTUS MENURUT KITAB YESAYA - Christie Kusnandar (Universitas Methodist Indonesia, 2017)
The presence of Christ as it is written in the Book of Isaiah, has some very interesting aspects of ethics to be observed and studied as an exemplary pattern of His life in the world, one of which is ministry. Long before Christ served, the prophecies of His ministry has been written by the prophet Isaiah is shown usHis existence in the world,as a series of mission that have been planned in a clearly good model, so that we can fully comprehend and apply the meaning of real ministry in daily life.